Development of a flat membrane microchannel packed-bed reactor for scalable aerobic oxidation of benzyl alcohol in flow - Wu, Gaowei; Cao, Enhong; Ellis, Peter; Constantinou, Achilleas; Kuhn, Simon; Gavriilidis, Asterios (My University, 2019)
A flat membrane microchannel reactor was designed and demonstrated for the safe and scalable oxidation of solvent-free benzyl alcohol with molecular oxygen on Au-Pd/TiO2 catalyst. The microchannel reactor employed a mesh-supported Teflon AF-2400 membrane, with gas and liquid channels on each side. Catalyst particles were packed in the liquid flow channel. Operation with 20 bara pressure difference between the gas and the liquid phases was possible at 120 °C. Pervaporation of organics through the membrane was experimentally measured to ensure that the organic vapour concentration remained below the lower flammability limit during the reaction. High oxygen pressure was shown to have a positive effect on reactor performance. A conversion of benzyl alcohol of 70% with 71% selectivity to benzaldehyde was obtained at 1150 gcat·s/galcohol, 8.4 bara oxygen pressure and 10 bara liquid pressure. The oxygen consumption rate was not significantly decreased when doubling the membrane thickness, indicating that the membrane generated only low resistance to oxygen mass transfer. When changing the catalyst particle size and the liquid flow rate, no significant effect was observed on the oxidation reaction rate. An effectiveness factor approach is proposed to assess the effect of oxygen permeation and transverse mass transfer on the catalyst packed in the membrane reactor, which suggests that the oxidation of benzyl alcohol on the highly active Au-Pd/TiO2 catalyst is controlled by the oxygen transverse mass transfer in the bulk liquid within the catalyst bed. Scale-up of the flat membrane microchannel reactor was demonstrated through increasing the liquid channel width by approximately ten times, which increased the reactor productivity by a factor of eight.
Keywords: Gold-palladium catalyst; Teflon AF-2400 membrane; Membrane microchannel reactor; Aerobic oxidation of alcohol; Effectiveness factor